Tanggap Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.)Varietas Lokal Samosir Terhadap Varietas Lokal Samosir Terhadap Beberapa Dosis Iradiasi Sinar Gamma - Puspa Hayati Sinambela,; Ferry Ezra Sitepu; Mariati Mariati (Jurnal Agroekoteknologi, 2015)
The aim of the research was to identify the effect on gamma ray irradiation on vegetative growthand production of local onion (Allium ascalonicum L.) Var. samosir. The research was conducted atJl. Pancing, Medan, North Sumatera, with a height of 25 m above sea level began from April up toJuly 2014. Bulbs of onion were exposed to various doses of gamma irradiation (0, 2, 4, 6, 8, 10, 12and 14 Gy) using Co60 source. Parameters observed were shoot length, leaves number, tillersnumber, harvesting age, bulb fresh weight, bulb dried weight, bulb diameter and average weight perbulb. The results showed significant difference between irradiated and unirradiated plants (control)growth and production. All parameter observed were lower than control. Irradiated plants 6 weeksafter planting at doses 6,8,10 12 Gy reduced shoot length 24.5%, 35.4%, 54.07%, 64.19%; leavesnumber 36.30%, 46.54%, 45.28%, 69.74%, respectively compared to control. There was no plantsustein alife at doses of 10, 12 and 14 in 7 weeks after planting. Irradiated plants at doses of 6 and 8Gy also reduced bulb fresh weight 56.40%, 70.85%, bulb dried weight 58.61%, 76.15%, bulbsdiameter 31,09% , 44.12%, average weight per tuber 59.6%, 78.45% respectively compared tocontrol.Keywords: onion, var. samosir, gamma ray irradiation